On the Design of Conical Antennas for Broadband Impedance Matching Performance - Francisco Estêvão Simão Pereira; Maurício Henrique Costa Dias (International Journal of Antennas and Propagation)
In the scope of broadband radiators, the biconical antenna, or its monopole conical counterpart, is long known to be a proper choice. One common form of such radiator, the spherically capped conical antenna (SCCA), has closed-form solution to its input impedance, from which the broadband performance potential is easily verified. Nonetheless, from the design perspective, apart from a few clues inferred from existing solutions, little is found to accurately guide the choice of the main geometrical parameters of the antenna that will enable it to comply with a set of imposed bandwidth requirements. This paper proposes a simple 10-step sequence to derive conical or biconical antenna design charts. These charts provide straightforward information on the geometrical limits within which the required antenna impedance matching broadband performance is achieved. The method is assessed for the SCCA and the open conical antenna (OCA) using theoretical and simulated estimates of the input impedance. A discussion on the impact of the cap and the feed gap is included.